Chronic and Recurrent Depression in Primary Care: Socio-Demographic Features, Morbidity, and Costs. (6th June 2012) - McMahon, Elaine M.; Buszewicz, Marta; Griffin, Mark; Beecham, Jennifer; Bonin, Eva-Maria; Rost, Felicitas; Walters, Kate; King, Michael
Abstract : Background . Major depression is often chronic or recurrent and is usually treated within primary care. Little is known about the associated morbidity and costs. Objectives . To determine socio-demographic characteristics of people with chronic or recurrent depression in primary care and associated morbidity, service use, and costs. Method . 558 participants were recruited from 42 GP practices in the UK. All participants had a history of chronic major depression, recurrent major depression, or dysthymia. Participants completed questionnaires including the BDI-II, Work and Social Adjustment Scale, Euroquol, and Client Service Receipt Inventory documenting use of primary care, mental health, and other services. Results . The sample was characterised by high levels of depression, functional impairment, and high service use and costs. The majority (74%) had been treated with an anti-depressant, while few had seen a counsellor (15%) or a psychologist (3%) in the preceding three months. The group with chronic major depression was most depressed and impaired with highest service use, whilst those with dysthymia were least depressed, impaired, and costly to support but still had high morbidity and associated costs. Conclusion . This is a patient group with very significant morbidity and high costs. Effective interventions to reduce both are required.